Minimum quantity of lubrication (MQL) as an eco-friendly alternative to the cutting fluids in advanced ceramics grinding - Javaroni, R. L. [UNESP]; Lopes, J. C. [UNESP]; Sato, B. K. [UNESP]; Sanchez, L. E. A. [UNESP]; Mello, H. J. [UNESP]; Aguiar, P. R. [UNESP]; Bianchi, E. C. [UNESP] (Springer, 2019)
Advanced ceramics have been extensively used in industry applications due to their properties of high resistance to wear and hardness. However, there is still a high added cost related to the workpiece finish, which is usually performed by the grinding process, the only economically viable process that produces surfaces of high quality and geometric precision. Companies have been looking for optimization in the grinding process, for example in the reduction of the cutting fluid used, in this case also in order to meet the world environmental preservation requirements, without compromising the quality of the finished part. In this context, the present research sought to exploit the technique of minimum quantity of lubrication (MQL) in the external cylindrical plunge grinding of ceramics with diamond grinding wheels. Two methods of cooling-lubrication were used: the conventional and MQL, with three different feed rates (V-f1, V-f2, and V-f3) for each condition. A conventional nozzle and a proper nozzle for MQL with uniform output jet were used. Variables were analyzed as the surface roughness, roundness deviation, scanning electron microscopy (SEM), G ratio, and output acoustic emission. The results showed that the conventional cooling-lubrication gives the best results for the output variables analyzed, comparing with the MQL. However, the MQL still presented satisfactory results that may be sufficient in several cases. Considering the economic, health, and environmental benefits presented by this technique, MQL comes as a strong tendency for ceramic grinding processes.
Keywords: Cylindrical grinding; Diamond wheel; MQL technique; Advanced ceramic; Surface integrity